Digital Political Branding: Instagram Strategy of Regional Head Candidates for Electoral Success in Indonesia 2024 - Arnandy, Taufik; Sutjiatmi, Sri; Harto, Unggul Sugi; Bhatti, Muhammad Safdar (Potret Pemikiran, 2024)
This research examines the transformation of political communication strategies in the digital era, specifically the use of Instagram by Tegal Regency's candidate Regents in the 2024 Regional Election. The high social media penetration in Indonesia, with 97% of Instagram users actively interacting, creates new opportunities and challenges in regional-level political communication. The research aims to analyze the digital personal branding strategies and political communication effectiveness of both candidates through Instagram. The research method employs a descriptive qualitative approach with social media content analysis using Nvivo 12 Pro, focusing on Instagram accounts @bimasakti19 and @ischak.mr during the September-October 2024 period. Research findings show significant strategy differences between the two candidates: @bimasakti19 implements an interactive approach with consistent hashtag #LOKENPANKAYAKIEBAE and actively reposts community support, while @ischak.mr focuses on field activity documentation and direct interaction. Word cloud analysis reveals the dominance of keywords related to public service and local issues. In conclusion, Instagram has become a vital instrument in local political communication transformation, creating a more dynamic dialogue space between candidates and voters, although still requiring balance between digital branding strategy and political message authenticity.